Urban sprawl within the Metropolitan Area of Oradea. - Carrière, Jean-Paul; Filimon, Luminita; Guitel, Sabine; Savourey, Cathy; Irincu, Elena (Routledge, 2018)
Urban sprawl has been subject to considerable research in western countries. However, there has been little analysis of its nature in the former communist countries because of its more recent development. Using a case study of Oradea as an illustration, this paper presents the key driving forces of the urban sprawl process in the city and emphasises the particular features of the phenomenon in the Romanian context. In countries like Romania urban development was constrained during the communist period, urban planning policies favouring a concentrated and high-density city. However, urban sprawl has expanded over the last ten years, triggered by the rejection of the former model but also by deregulation: many restrictions inherited from the former regime have been abolished. Since 2001, despite demographic decline, there has been a general expansion of residential areas in all suburban communes, a process which has not been restricted to the periphery of the cities, but has also proceeded by "leapfrogging" over peripheral urban land. The paradox of Oradea is expressed through a combination of strong demographic decline with a late, but rapid, urban sprawl, with most municipalities of the metropolitan area ill-equipped to manage new suburban development in the less regulated context of a market-led economy.
Keywords: Siedlungsentwicklung; Stadtregion; Regionalentwicklung; Stadtwachstum; Flächennutzung; Nutzungsänderung; Siedlungsfläche; Urban Sprawl; Urbanismus; Stadtregion; Postsozialismus; Transformationsprozess; Immobilienmarkt; Deregulierung